Teoretične prvine političnega pravoznanstva - Spruk, Jure (Teorija in praksa, 2024)
The article discusses political jurisprudence; namely, the discipline of political science that studies the working of the courts. Political jurisprudence has three core characteristics: (1) law is a means for achieving political goals; (2) the courts are political institutions and the judges are political actors; and (3) law is created rather than discovered by the judges. These characteristics are opposed to the image of legal neutrality, which presupposes value and social isolation. Instead, it supports the image of ideologically based law that is politically biased with respect to political doctrines, but not in relation to daily political struggles. Emphasis is given to the highest courts – constitutional courts – which frequently decide politically delicate cases in constitutional democracies. From the point of view of political jurisprudence, the best criteria for the prediction of a judge’s votes are their ideological preferences.
Keywords: law; political jurisprudence; politics; politično pravoznanstvo; politika; Pravo; Pravo in politika